A case of large cervical lipoleiomyoma simulating malignancy: an intraoperative dilemma - Agrawal, Priti; Agrawal, Rishi; Lobo, Anandi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Primary lipomatous tumors of the uterus are very unusual benign neoplasms with an incidence of 0.03% to 0.2%. Most commonly described in the uterine corpus, lipoleiomyomas (LLM) have been reported in cervix, broad ligament and retro peritoneum. Here we report a case of perimenopausal women with cervical LLM which was highly friable simulating cervical malignancy, creating an intraoperative dilemma. A 45 year old perimenopausal woman presented with severe abdominal pain with difficulty in passing urine and motion, excessive bleeding per vaginum with increased frequency of menses, since 6 months. Ultrasonography revealed a well-defined rounded to oval heterogeneous hyperechoic lesion with minimal vascularity measuring 10.4×11.0×7.7 cm, volume-469 cc, probably arising from anterior lip of cervix. Patient was taken for laparotomy. Intraoperative friability and vascularity of the mass was suggestive of malignancy. LLM, if asymptomatic, requires no treatment. But symptomatic cases require surgical management.